Ethnography #9 - Klima, Alan (Duke University Press, 2019)
As Alan Klima writes in Ethnography #9, "there are other possible starting places than the earnest realism of anthropological discourse as a method of critical thought." In this experimental ethnography of capitalism, ghosts, and numbers in mid- and late-twentieth-century Thailand, Klima uses this provocation to deconstruct naive faith in the "real" and in the material in academic discourse that does not recognize that it is, itself, writing. Klima also twists the common narrative that increasing financial abstractions in economic culture are a kind of real horror story, entangling it with other modes of abstraction commonly seen as less "real," such as spirit consultations, ghost stories, and haunted gambling. His unconventional, distinctive, and literary form of storytelling uses multiple voices, from ethnographic modes to a first-person narrative in which he channels Northern Thai ghostly tales and the story of a young Thai spirit. This genre alchemy creates strange yet compelling new relations between being and not being, presence and absence, fiction and nonfiction, fantasy and reality. In embracing the speculative as a writing form, Klima summons unorthodox possibilities for truth in contemporary anthropology.